The Correctional Institution Recommendation As Judge's Consideration In Making A Decision Against Child Narcotics Abuser - Novalinda Nadya Putri; Somawijaya Somawijaya; Agus Takariawan (Jurnal Ilmiah Galuh Justisi, 2021)
Recalling that children are individuals who are still emotionally unstable but have become legal subjects, so the handling of narcotics abuse cases committed by children needs special attention and protection from the state. However, in deciding the case of the child, the judge has things that are often taken into consideration, such as the results of community research which later become the basis for the recommendation of the Correctional Center as regulated in Article 60 paragraph (3) of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. This study examines the recommendations of the Correctional Center as a judge's consideration in making decisions against children who abuse narcotics. The research method used in this research is descriptive analysis. The purpose of this study was to determine the role of the correctional center in juvenile criminal justice and the recommendations of the correctional center as a judge's consideration in making decisions against children who abuse narcotics. Correctional Centers have an important role in the success of the juvenile criminal justice system, namely by providing assistance, guidance, coaching, and supervision of children who are dealing with the law The goal of the juvenile justice system can be achieved maximally, namely to ensure the protection of the best interests of the child. In making a decision on a child who abuses narcotics, the Judge has considered the recommendation of the Correctional Center, but the judge did not heed the recommendation of the Correctional Center. This can be seen in several decisions in cases of child drug abusers who are still sentenced to prison by the judge, where the recommendations of the Correctional Center tend to suggest imposing sanctions of treatment against children. The judge should give priority to the best interests of the child to avoid imprisonment as referred to in the recommendation of the Correctional Center by using the independence and freedom of the judge.